2000
DOI: 10.1177/009127000004001204
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐State Pharmacodynamics and Pharmacokinetics of Warfarin in the Presence and Absence of Telmisartan in Healthy Male Volunteers

Abstract: The effects of multiple‐dose telmisartan on the steady‐state pharmacodynamics and pharmacokinetics of warfarin were assessed in 12 healthy young males in an open‐label, single‐period study conducted over 30 days. Subjects received loading doses of oral once‐daily warfarin on days 1 to 5, which were individually adjusted at days 6 and/or 9 to attain stable predose prothrombin time values (INRpre) of between 1.2 and 1.8 by the end of medication phase 1 (day 14). From days 15 to 24 (medication phase 2), subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The finding of this study indicated that specific chemical structures of ARBs significantly affected their affinity to the CYP2C9 enzyme, exerting inhibitory effects on the enzyme. However, a 30-day open-label, single-period study reported that telmisartan treatment reduced mean warfarin trough plasma concentration but did not change the INR [ 44 ]. Therefore, the impact of ARBs on the requirements of stable warfarin doses remains unclear, and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of this study indicated that specific chemical structures of ARBs significantly affected their affinity to the CYP2C9 enzyme, exerting inhibitory effects on the enzyme. However, a 30-day open-label, single-period study reported that telmisartan treatment reduced mean warfarin trough plasma concentration but did not change the INR [ 44 ]. Therefore, the impact of ARBs on the requirements of stable warfarin doses remains unclear, and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%